2021
DOI: 10.1371/journal.pone.0254634
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of autoimmune bullous diseases in Sudan between 2000 and 2016

Abstract: Objectives Autoimmune bullous diseases vary in their clinico-epidemiological features and burden across populations. Data about these diseases was lacking in Sudan. We aimed to describe the epidemiological profile and to estimate the burden of autoimmune bullous diseases in Sudan. Methods This was a retrospective cross-sectional study conducted at Khartoum Dermatological and Venereal Diseases Teaching Hospital. We used routinely collected health care data, and included all patients with an autoimmune bullous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
(241 reference statements)
1
0
0
Order By: Relevance
“…None of the patients in our study had bullous systemic lupus erythematosus. However, this is consistent with the epidemiology of AIBD in adults in which pemphigus is observed to be the most frequent AIBD in studies from Iran, Greece, and Sudan 5–7 . The variation in the spectrum of AIBD in our study as compared to the previous studies in the pediatric population can be attributed to the genetic variations in different populations, and environmental factors such as dietary habits (use of garlic, etc.)…”
Section: Discussionsupporting
confidence: 91%
“…None of the patients in our study had bullous systemic lupus erythematosus. However, this is consistent with the epidemiology of AIBD in adults in which pemphigus is observed to be the most frequent AIBD in studies from Iran, Greece, and Sudan 5–7 . The variation in the spectrum of AIBD in our study as compared to the previous studies in the pediatric population can be attributed to the genetic variations in different populations, and environmental factors such as dietary habits (use of garlic, etc.)…”
Section: Discussionsupporting
confidence: 91%
“…This was similar to reports in the literature indicating that DH most often develops between the second and seventh year of life, as found by Ermacora et al [10]. Other studies, however, have shown a predominance of DH in adults aged between 25.6 and 66 years [2,5,6,11].…”
Section: Epidemiologysupporting
confidence: 91%
“…Coast and in Sudan found a prevalence of 20.9 for 100,000 patients [4] and 5 cases in 16 years [5], respectively. In view of the rarity of African data and the difficulties of diagnosis in our context, we undertook the present study to document the sociodemographic, clinical, and therapeutic aspects of DH in a hospital setting.…”
mentioning
confidence: 99%
“…One case report describes an interesting case of induced autoimmunity, preventing pemphigus despite the patient having Hodgkin's lymphoma, a risk factor for pemphigus [50]. Other suggested risk factors are sex thymic diseases, and P wave dispersion increases and diversity of diet intake [51][52][53][54].…”
Section: Pemphigusmentioning
confidence: 99%